Differences Between the Effects of The Benson Relaxation Technique and Deep Breath on Anxiety, Sleep Quality, and Fatigue in Hemodialysis Patients - Dedi Krismiadi; Titin Andri Wihastuti; Dina Dewi Sartika Lestari Ismail (Universitas Aisyah Pringsewu, 2023)
Psychological and physical problems often occur in hemodialysis patients such as anxiety, sleep quality and fatigue which if not treated immediately, can reduce the patient's quality of life. Benson relaxation and deep breathing can lower anxiety, sleep quality, and fatigue in hemodialysis patients. With decreased anxiety, higher sleep quality and decreased fatigue, the patient's quality of life could be enhanced. This study aims to determine the differences in anxiety, sleep quality and fatigue in hemodialysis patients treated using the Benson relaxation technique and deep breathing. The research method used quasi-experimental on several 52 respondents who were selected through the simple random sampling technique and were divided into 2 intervention and control groups. The Kruskal-walis test showed that the p-value = 0.000 less than 0.05 was obtained in anxiety. The difference rank value is higher in the Benson relaxation of 37.96. on sleep quality, p-value = 0.000 less than 0.05. The rank difference is higher in the Benson relaxation of 34.56. At the same time, the data management results on fatigue obtained a p-value = 0.014 less than 0.05. The difference in Rank value is higher in the Benson relaxation of 34.56. It can be concluded that Benson's relaxation therapy can reduce anxiety, sleep quality, and fatigue because it uses spiritual values that can improve the quality of life of hemodialysis patients. Abstrak: Masalah psikologis dan fisik sering terjadi pada pasien hemodialsis seperti kecemasan, kualitas tidur dan kelelahan yang apabila tidak segera untuk ditangani dapat menurunkan kualitas hidup pasien. Relaksasi yang dapat dilakukan untuk menurunkan kecemasan, kualitas tidur dan kelelahan pada pasien hemodialisis adalah dengan melakukan relaksasi Benson dan napas dalam. Dengan menurunnya kecemasan, meningkatnya kualitas tidur dan menurunnya kelelahan dapat meningkatkan kualitas hidup pasien. Penelitian ini bertujuan untuk mengetahuai perbedaan kecemasan, kualitas tidur dan kelelahan pada pasien hemodialisis yang diterapi menggunakan teknik relaksasi Benson dan napas dalam. Metode penelitian menggunakan quasi eksperimen pada sejumlah 52 responden yang terpilih melalui teknik simple random sampling dan dibagi menjadi 2 kelompok intervensi dan kontrol. uji kruskal walis menunjukkan bahwa pada kecemasan, didapatkan nilai p-value= 0.000 kurang dari 0.05. nilai rank selisih lebih tinggi pada relaksasi benson sebesar 37.96. pada kualitas tidur, didapatkan nilai p-value= 0.000 kurang dari 0.05. Rank selisih lebih tinggi pada relaksasi Benson sebesar 34.56. Sedangkan Hasil pengelolaan data pada kelelahan, didapatkan nilai p-value= 0.014 kurang dari 0.05. Nilai Rank selisih lebih tinggi pada relaksasi Benson sebesar 34.56. Dapat disimpulkan bahwa terapi relaksasi Benson dapat menurunkan kecemasan, meningkatkan kualitas tidur dan menurunkan kelelahan lebih baik karena menggunakan nilai spiritual yang dapat meningkatkan kualitas hidup pasien hemodialisis.